ERSEPSI GURU DALAM PENGGUNAAN METODE STORYTELLING INTERAKTIF BERBANTUAN MEDIA CANVA: IMPLIKASINYA DALAM KETERAMPILAN MENYIMAK DI SEKOLAH DASAR - Zulhendri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study focuses on elementary school teachers’ perceptions of the use of interactive storytelling methods assisted by Canva media and its implications for the listening skills instruction of elementary school students. The purpose of this study is to understand elementary school teachers’ perceptions of the use of interactive storytelling methods assisted by Canva media and their implications for teaching listening skills in elementary education. This research employs a quantitative approach used a survey method, with questionnaires as the primary data collection tool. The populations in this study consists of 132 elementary school teachers, with a sample of 100 teachers. Based on the results, it is concluded that for positively stated items, teachers strongly agreed at 50% and agreed at 50%. Meanwhile, for negatively stated items, 97% of teachers disagreed with the statements regarding the use of interactive storytelling methods assisted by Canva media and its implications for teaching listening skills to elementary students.